Effect of reinforcing and crack width on the vibration damping capacity of rubberized concrete beams. (3rd November 2022) - Liu, Royce; Palermo, Alessandro; Chiaro, Gabriele
Abstract: The damping of simply supported rubberized concrete beams was measured and compared against conventional concrete beams in their uncracked and cracked states. The variables controlled were: rubber content (10% and 20% by total volume of aggregates replaced), reinforcing content, axial load, and damage state. Impact hammer‐induced free‐vibration was used to excite the specimens and quasi‐static four‐point bending used to damage the beams. Rubberized concrete displayed a measurable increase in damping relative to ordinary concrete in both the uncracked and cracked states. It was found that reinforcing appears to reduce the damping of all beam specimens in their undamaged state compared to unreinforced counterparts. No relationship was found between reinforcing ratio and damping. For crack widths up to 0.1 mm a non‐linear monotonic increase in damping was observed. Damping measured throughout the entire pushover response of the beams was found to follow a skewed‐shaped bell curve. Compressive axial load was found to reduce the damping of the beams. The shape of the free vibration decay envelopes was examined. Rubber was found to make the damping response more viscous‐like. Whilst reinforcing made the shapes of the decay curves more similar between beams made of different concrete types. No clear evidence for friction damping due to cracking was found. For all beams, based on the free‐vibration response, it was found that the damping exhibited by both plain and reinforced concrete is not a true exponential decay curve. This means that the damping calculated by the logarithmic decrement method will depend on the choice of interval selected. A method for standardizing the implementation of the logarithmic decay method to avoid arbitrary choices of intervals and allow for fairer cross‐study comparison of damping values was therefore proposed.